Clinical and experimental validation of a capnodynamic method for end‐expiratory lung volume assessment. Issue 5 (30th January 2020) - Öhman, Tomas; Sigmundsson, Thorir S.; Hallbäck, Magnus; Suarez Sipmann, Fernando; Wallin, Mats; Oldner, Anders; Björne, Håkan; Hällsjö Sander, Caroline
Abstract : Introduction: Lung protective ventilation can decrease post‐operative pulmonary complications. The aim of this study was to evaluate a capnodynamic method estimating effective lung volume (ELV) as a proxy for end‐expiratory lung volume in response to PEEP changes in patients, healthy subjects and a porcine model. Methods: Agreement and trending ability for ELV in anaesthetized patients and agreement in awake subjects were evaluated using nitrogen multiple breath wash‐out/in and plethysmography as a reference respectively. Agreement and trending ability were evaluated in pigs during PEEP elevations with inert gas wash‐out as reference. Results: In anaesthetized patients bias (95% limits of agreement [LoA]) and percentage error (PE) at PEEP 0 cm H2 O were 133 mL (−1049 to 1315) and 71%, at PEEP 5 cm H2 O 161 mL (−1291 to 1613 mL) and 66%. In healthy subjects: 21 mL (−755 to 796 mL) and 26%. In porcines, at PEEP 5‐20 cm H2 O bias decreased from 223 mL to 136 mL LoA (34‐412) to (−30 to 902) and PE 29%‐49%. Trending abilities in anaesthetized patients and porcines were 100% concordant. Conclusion: The ELV‐method showed low bias but high PE in anaesthetized patients. Agreement was good in awake subjects. In porcines, agreement was good at lower PEEP levels. Concordance related to PEEP changes reached 100% in all settings. This method may become a useful trending tool for monitoring lung function during mechanical ventilation, if findings are confirmed in other clinical contexts.